The reliability and validity of various lateral side-step tests - McCormick, B. T. (International Journal of Applied Sports Sciences, 2014)
The ability to change directions, cut, and move quickly is paramount to success in basketball. Lateral shuffling movements or side-steps are common in basketball, but few tests incorporate these movements in measures of change-of-direction speed. Furthermore, no reliability or validity information has supported the most popular test, the Edgren Side-Step Test, and the procedures for the Edgren Test have been inconsistent. This study examined 4 lateral shuffle tests (LST), which combined different distances (8 feet and 12 feet) and durations (6 seconds and 10 seconds). All 4 conditions of the LST had very good internal consistency as the Cronbach's Alpha for each was above 0.889. All 4 conditions had very good test-retest reliability as the ICC (3,1) for each was above 0.930. None of the 4 conditions was found to have a significant relationship with a 20m sprint, whereas the 8x10-LST, r = - 0.640, p = 0.046 and the 8x6-LST, r = - 0.648, p = 0.043 had a moderate negative relationship with the Hexagon Agility Test. No condition was found to be a discriminator between recreational and competitive basketball players. Based on the results, the LST-8x6 and LST-8x10 appear to be valid and reliable tests for measuring change-of-direction speed.